ANALISIS TINGKAT KEAMANAN PANGAN PADA UMKM WILAYAH PERKOTAAN: Analisis Keamanan Pangan UMKM Wilayan Perkotaan - Irwanto, Reno; Amrizal, Sri Novalina (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2024)
Food safety is essential in maintaining consumer health, especially in urban areas with high and diverse consumption levels. This study aims to analyze the level of food safety in MSMEs using the Food Safety Score (SKP) approach, which includes four main aspects: Selection and Storage of Food Ingredients (PPB), Cooking Hygiene (HGP), Food Processing (PBM), and Food Distribution (DMP). This research method is descriptive observational with data collection through direct observation, interviews, and assessments using the SKP form. Data were taken from six East Jakarta and Central Jakarta MSMEs in March-April 2024. The results showed that the SKP scores varied among MSMEs, with MSME D having the highest score (0.99) and MSME B having the lowest (0.54). The PBM and DMP aspects are the main weak points that increase the risk of contamination, while the PPB aspect generally shows good compliance. This study concludes that although some MSMEs have met food safety standards, improvement efforts are still needed in the processing and distribution aspects to improve product quality and consumer protection. Recommendations include training, supervision, and provision of adequate sanitation facilities. The results of this study are expected to contribute to MSMEs, the government, and policymakers in designing more effective coaching programs to create a safe and sustainable food ecosystem.